2008
DOI: 10.1186/1465-9921-9-60
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase reduces secretion of secretory leukoproteinase inhibitor (SLPI) by lung epithelial cells: role of charge of the proteinase-inhibitor complex

Abstract: Background: Secretory leukoproteinase inhibitor (SLPI) is an important inhibitor of neutrophil elastase (NE), a proteinase implicated in the pathogenesis of lung diseases such as COPD. SLPI also has antimicrobial and anti-inflammatory properties, but the concentration of SLPI in lung secretions in COPD varies inversely with infection and the concentration of NE. A fall in SLPI concentration is also seen in culture supernatants of respiratory cells exposed to NE, for unknown reasons. We investigated the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…However, protease levels only accounted for a maximum of 23% of the variance in sputum SLPI levels, suggesting an important contribution from reduced SLPI production. In addition, our data demonstrates that elastase reduces release of SLPI from epithelial cells independent of its protease activity, as previous data suggested (21). Other studies have generated a variant of SLPI resistant to degradation by neutrophil elastase (32).…”
Section: Discussionsupporting
confidence: 85%
“…However, protease levels only accounted for a maximum of 23% of the variance in sputum SLPI levels, suggesting an important contribution from reduced SLPI production. In addition, our data demonstrates that elastase reduces release of SLPI from epithelial cells independent of its protease activity, as previous data suggested (21). Other studies have generated a variant of SLPI resistant to degradation by neutrophil elastase (32).…”
Section: Discussionsupporting
confidence: 85%
“…Results from studies with these patients suggest that an inverse correlation exists between SLPI levels and the risk of developing an exacerbation [40]. Interestingly, our group has recently shown that 17β-oestradiol (E 2 ), the primary oestrogen in non-pregnant females, is capable of abrogating TLR (Toll-like receptor) responsiveness by up-regulating SLPI in CF bronchial epithelial cells (Figure 2).…”
Section: Slpi Inflammatory Lung Disease and The Female Gendermentioning
confidence: 93%
“…34 However, extracellular levels in tissue cultures and in respiratory secretions are low. 35 SLPI forms complexes with elastase, and such complexes are bound to negatively charged cell membranes, decreasing levels in free secretions. 35 Bacterial infection in COPD is a strong stimulus for increased proteolytic activity in the lower respiratory tract, which is the most likely mechanism of the decreased SLPI levels seen in this study.…”
Section: Effect Of Acquisition Of a New Bacterial Strain On Sputum Ammentioning
confidence: 99%